Influence of different curing temperatures and alkali activators on properties of GBFS geopolymer mortars containing fly ash and palm oil fuel ash - Ghasan, Fahim Huseien (ELSEVIER, 2016)
This paper reports the influence of different curing temperatures, calcium content and different types of alkali activator solutions on properties of geopolymer mortars (GPM) containing industrial and agricul- tural wastes, such as granulated blast furnace slag (GBFS), fly ash (FA) and palm oil fuel ash (POFA). Three kinds of GPM were prepared using activated solutions of sodium hydroxide (NH) with sodium silicate (NS), NS alone, and sodium silicate plus water (NSW). All these mixtures were subjected to eight molar (8 M) concentration of NH solution, alkaline liquid to binder ratio of 0.30, NS to NH ratio of 3.0, binder to fine aggregate ratio of 1.5 at different curing temperatures of 27, 60 and 90 ° C. Results revealed that the reaction products and the GPM strengths depended strongly on the nature of compositions, acti- vators and curing temperatures. Alkaline activators formed a crystalline calcium silicate hydrate (CSH) which co-existed with amorphous gel. The observed enhancement in the compressive strength and the microstructure of GPM was attributed to the creation of extra CSH with increasing calcium content. A cor- relation between the compressive strength and the main product of geopolymerization process, namely, sodium aluminosilicate hydrate (NASH) gel was established based on the bond between Portland cement concrete substrate and GPM.